Staphylococcus aureus uses the bacilliredoxin (BrxAB)/bacillithiol disulfide reductase (YpdA) redox pathway to defend against oxidative stress under infections - Linzner, Nico; Wirtz, Markus; Hell, Rüdiger (Frontiers in microbiology, 2019)
Staphylococcus aureus is a major human pathogen and has to cope with reactive oxygen and chlorine species (ROS, RCS) during infections. The low molecular weight thiol bacillithiol (BSH) is an important defense mechanism of S. aureus for detoxification of ROS and HOCl stress to maintain the reduced state of the cytoplasm. Under HOCl stress, BSH forms mixed disulfides with proteins, termed as S-bacillithiolations, which are reduced by bacilliredoxins (BrxA and BrxB). The NADPH-dependent flavin disulfide reductase YpdA is phylogenetically associated with the BSH synthesis and BrxA/B enzymes and was recently suggested to function as BSSB reductase (Mikheyeva et al., 2019). Here, we investigated the role of the complete bacilliredoxin BrxAB/BSH/YpdA pathway in S. aureus COL under oxidative stress and macrophage infection conditions in vivo and in biochemical assays in vitro. Using HPLC thiol metabolomics, a strongly enhanced BSSB level and a decreased BSH/BSSB ratio were measured in the S. aureus COL 1ypdA deletion mutant under control and NaOCl stress. Monitoring the oxidation degree (OxD) of the Brx-roGFP2 biosensor revealed that YpdA is required for regeneration of the reduced BSH redox potential (EBSH) upon recovery from oxidative stress. In addition, the 1ypdA mutant was impaired in H2O2 detoxification as measured with the novel H2O2-specific Tpx-roGFP2 biosensor. Phenotype analyses further showed that BrxA and YpdA are required for survival under NaOCl and H2O2 stress in vitro and inside murine J-774A.1 macrophages in infection assays in vivo. Finally, NADPH-coupled electron transfer assays provide evidence for the function of YpdA in BSSB reduction, which depends on the conserved Cys14 residue. YpdA acts together with BrxA and BSH in de-bacillithiolation of S-bacillithiolated GapDH. In conclusion, our results point to a major role of the BrxA/BSH/YpdA pathway in BSH redox homeostasis in S. aureus during recovery from oxidative stress and under infections.
Gesehen am 14.01.2020